Preparação e caracterização de compósitos de polipirrol (LiMn2O2)/ fibra de carbono para catodos em baterias secundárias - Kaibara, Patrícia Silvestre de Oliveira (Universidade Federal de São Carlos, 2003)
Composites of polypyrrol (Ppy) and LiMn2O4 were synthesized chronoamperometrically at 0.8 V (vs. ECS) in 0.1 mol.L-1 LiClO4 /acetonitrile (2% H2O added) electrolyte containing 0.1 mol.L-1 of the pyrrol monomer, on carbon fiber (CF) substrates. The optimum concentration of the oxide in the electrolyte was found as 0.12 g.L-1. Both the previous ultrassonic dispersion of the oxide and the electrolyte mechanic stirring during the synthesis led to the best composite properties. For comparison, other composites were also prepared: Ppy/CF; Ppy(PSS)/CF and Ppy(PSS)/LiMn2O4/CF. Electrochemical stability tests were performed by cyclic voltammetry for all composites, in the electrosynthesis electrolyte without the monomer and water as well as in 0.1 mol.L-1 LiClO4 / propilene carbonate. The morphology, coupled with elemental analysis, and the electrical properties of all composites were obtained, respectively, by SEM/EDS and impedance spectroscopy. The discharge capacity obtained for the Ppy/LiMn2O4/CF composite was 80 mA.h.g-1, about 100% higher than the one for the Ppy/CF composite. The capacity value found for Ppy(PSS)/CF was similar, but the charge/discharge runs presented a slow profile to reach the maximum steady value, which is not interesting for cathode in rechargeable batteries. On the other hand, the Ppy(PSS)/LiMn2O4/CF composite showed the smaller capacity value. Therefore, among all the analyzed composites, the one containing Ppy and LiMn2O4 presented the best performance to be used as cathodes in lithium ion batteries.
Polypyrrol (LiMn204)/ carbon fiber composites as cathodes in rechargeable batteries
Keywords: Baterias secundárias; Polímeros condutores; Compósitos poliméricos; Polipirrol; Óxido de manganês; Fibra de carbono; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA